Analisis Kandungan Merkuri (Hg) Pada Lotion Dengan Klaim “Dosis Tinggi” Yang Dijual Di E-Commerce Shopee Daerah Jawa Tengah - Eko Hidayaturohman Khumaeni; Jaselin Felisiana (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2024)
Lotion with high doses claim is a mixture of chemicals or other ingredients that can whitening the skin quickly and moisturize skin. Mercury is one of the most harmful ingredients that often added in whitening lotion. The presence of metallic mercury (Hg) in whitening lotion product is very dangerous for the body health. This research aims to determine the mercury content in lotion with high doses claim that are not register in BPOM circulating at e- commerce Shopee in Central Java. The method used for this research is performed descriptively with the independent variable represented by lotion with high dose claim and the dependent variable represented by the presence of mercury content in the sample. This research include several stages of sample collection, implementation of mercury analysis and data analysis with 0.5 N KI and 2 N NaOH reagents. The results of this research indicate that 6 samples of lotion with high doses claim sell at e- commerce Shopee in Central Java not identified as contain mercury. The test result with 0.5 N KI and 2 N NaOH are different from the reference standard. From the research that has done on cosmetic lotion preparation with high doses claim, it can conclusion the six negative samples contain mercury.